Malibay cenaculo - Icasiano, Carmita Eliza I.; Malibay Culture & Arts Foundation, Inc.; Cultural Center of the Philippines (Pasay City Cultural Center of the Philippines, Museo ng Kalinangan Pilipino, 2003)
Catalogue of the exhibit Malibay cenaculo : isang siglo ng pamana at panata, at the Cultural Center of the Philippines from February 5 to March 30, 2003.
CD-ROM.
Keywords: Passion-plays -- Malibay (Pasay City) -- Exhibitions; Passion-plays -- Malibay (Pasay City) -- Exhibitions -- Catalogs